[Re]Conhecendo a habitação de vilas operárias em Iguatu-Ce na primeira metade do Século XX - Teles, Lúcia de Fátima Cavalcante (2021)
This thesis deals with a dialogue about housing in the countryside of Ceará in the city of Iguatu, of workers' villages built by Companhia Industrial de Algodão e Óleos (CIDAO) for its employees. [Re]endorsing these houses as material synthesis of the historical, economic and social conditions of this rural industrialization and its cultural aspects – typology, interior space, materials, construction techniques – two periods of experience will be worked: the first construction of the villages, and in a later moment its expansion: from 1930 to 1940 and from 1950 to 1965. The importance of this study is justified by the little importance given to the housing issue; in particular, the workers' villages in the history of Ceará's architecture and the housing reform from historical peculiarities opposing peasant struggles.